Association of Different Risk Factors with Iron Deficiency Anemia in Children - Novera Khalid, Afsheen Batool Raza, Aimen Javed, (Pakistan Journal of Medical & Health Sciences, 2024)
Iron Deficiency Anemia (IDA) arises from an imbalance in the body's iron production and demand, making it a prevalent form of anemia in children. While its causes are varied, many contributing factors to IDA are adjustable. If identified and addressed promptly, these factors can be modified to improve both immediate and extended health effects in children. 13It is an established fact that iron is an important component for growth of body and our nervous system. IDA in children may permanently disturb their sensory and cognitive ability. It is therefore important to determine its risk factors to ensure early screening and prevention among children. Aim and Objective: To determine correlation of different risk factors with Iron deficiency Anemia. Material and Methods: This case-control study, comprising 150 participants in each group, was carried out in the Pediatric department of Jinnah Hospital Lahore over a nine-month period, spanning from May 1, 2022, to January 31, 2023. Inclusion criteria involved children aged between 6 months and 12 years. Non-Probability consecutive sampling was employed to collect data, with informed consent obtained from parents/guardians. A pre-designed proforma was utilized for data collection. Statistical analysis using SPSS v.22 involved calculating mean and standard deviation for quantitative data, and presenting frequency and percentages for categorical data. Risk assessment and association were determined using odds ratio and chi-square tests, with a p-value below 5% considered significant. Results: The mean age of cases and controls was 8.47 ± 3.91 years and 8.41 ± 4.08 years respectively with 55% males. The mean Hb in cases was 8.84 ± 1.13 g/dL and in controls was 11.77 ± 3.28 g/dL. There were 71(47.3%) mothers in cases and 26(17.3%) in controls groups who were illiterate (p-value < 0.0001 & OR = 4.286), 80(53.3%) cases and 45(30%) controls that had family size > 5 (p-value < 0.0001 & OR = 2.667), and 67(44.7%) cases and 29(19.3%) controls had a history of cow milk usage ( p-value < 0.0001 & OR = 3.368). Significant association was found of the IDA with each risk factor in each strata (p-value <0.05) but there was no significant association between IDA and cow milk in females ( p-value > 0.05). Conclusion: There is significant association of IDA with illiteracy of mothers, family size > 5 and usage of cow milk. IDA can be minimized by improving these conditions in order to minimize further morbidities related to IDA. Keywords: Iron deficiency anemia, Cow milk, Illiteracy, Family size.